Indoor WIFI localization on mobile devices - Sujittra Boonsriwai (2018)
Indoor WIFI localization is challenging especially when deployed over wireless device with limited system resource. Although GPS can give approximate position of the mobile users, it is usually limited indoor due to the degradation of signals by the building structures. While various alternative WIFI localization techniques have been proposed for indoor uses, accurate results are hard to achieve due to the instability nature of wireless signal. In this paper, we discuss the performance of multi-trilateration and fingerprinting localization techniques in the context of mobile applications. The implementation of WIFI localization on mobile allows the users with WIFI-enable devices such as smartphone to locate their position and/or navigate themselves within the building. During our experiments, we noted that the selection criteria that involves selecting available access points to be used as a reference position considerably affect the accuracy of the positioning calculation. The tradeoff between multi-trilateration and fingerprinting in terms of correctness, computational complexity and system resource consumption have been discussed. Additionally, we proposed the suitable configuration for these localization algorithms as a means to achieve more accurate positioning results. © 2013 IEEE.